Penentuan diagnosis dalam perawatan saluran akar gigi 36 dengan radix entomolarisDiagnosis determination in the treatment of root canal teeth 36 with radix entomolaris - Pratami, Risa; Zakaria, Myrna Nurlatifah (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2018)
Pendahuluan: Radix entomolaris (RE) merupakan sebuah variasi anatomi normal gigi molar pertama rahang bawah yang mempunyai akar tambahan pada sisi lingual. Keberadaan RE seringkali tidak terlihat secara klinis, sehingga dapat mempengaruhi keberhasilan perawatan endodontik. Laporan kasus ini bertujuan untuk membahas mengenai penentuan diagnosis dan perawatan saluran akar gigi 36 yang memiliki radix entomolaris. Laporan kasus: Laporan kasus ini membahas mengenai pemeriksaan serta diagnosis RE pada gigi molar pertama kiri rahang bawah melalui teknik modifikasi sudut horizontal radiografi (horizontal tube shifting) dan menerapkan hukum orifis untuk melokalisasi saluran akar gigi dengan RE. Deteksi, diagnosis, dan perawatan yang sesuai pada RE menjadi hal penting untuk mencapai keberhasilan perawatan. Beberapa teknik untuk mengetahui keberadaan RE antara lain dengan modifikasi sudut horizontal dari cone beam pada pemeriksaan radiografi. Pemahaman mengenai outline akses pulpa yang berbentuk kotak atau trapesium, meluas hingga aspek distal-lingual juga merupakan tanda khas untuk melokalisasi orifis dari akar ini. Simpulan: Penentuan diagnosis dengan teknik modifikasi sudut horizontal radiografi (horizontal tube shifting) sebagai diagnosis awal yang akurat akan mencegah komplikasi dan tertinggalnya saluran akar RE saat perawatan saluran akar.Â ABSTRACTIntroduction : Radix entomolaris (RE) is a normal anatomic variation of mandibular first molar with an additional root in lingual aspect. The existence of RE clinically affects endodontic treatment, therefore detection, diagnosis, and proper treatment of RE are important to achieve a successful treatment. Modification in horizontal angle of cone beam during dental radiography can be utilized to confirm this anatomic variation. Rectangular or trapezium outline form of cavity, extends to distal-lingual aspect, can be made to locate this rootâs orifice. Meticulous examination, proper dental radiography technique, and accurate initial diagnosis will prevent the complications and missed canals of RE during root canal treatment which will lead to endodontic failures. Case Report: This case report discussed and reviewed the examination and diagnosis of radix entomolaris in permanent mandibular left first molar diagnosed through modification of radiography technique (horizontal tube shifting) and the application of orifice root map guidance to locate the additional root canal. Detection, diagnosis, and appropriate treatment of RE were essential for achieving a successful treatment. Some techniques to determine the existence of RE included modification of the horizontal angle of the cone beam on radiographic examination. An understanding of the pulp access outline that was square or trapezoidal, extending to the distal-lingual aspect was also a distinctive sign for localising the orifice from this radicular part. Conclusion: Determination of diagnosis by modifying the horizontal radiographic angle technique (horizontal tube shifting) as an accurate initial diagnosis will prevent complications and the loss of the RE root canal during root canal treatment.Â Keywords: Root canal treatment, radix entomolaris, horizontal tube shifting.